Efficacy of family-based care as compared to institutional care: a careful review - K. Bhuvaneswari; Sibnath Deb (Scottish Journal of Residential Child Care)
Family is the nucleus of the society and children are the nucleus of the family. Children are referred as supremely national asset of India. When children are in situation where family finds it difficult to protect their rights, Institutions intercede and protect as well as violate the rights of children. A significant portion of child population ranging from two to eight million in Africa, Asia, Latin America and in Eastern Europe are under institutional care . Children in institutional care are often termed as "No one's children", "Nobody's children" as they are given least attention by the institution as well as society. An attempt is made to understand the functioning of institution in protecting the rights of children who are in need of care and protection. The measures for revamping the institutional care and revolutionizing family care were highlighted.